Secure Exposure of REST APIs in Homelab Environments using Cloudflare Tunnel - Guedes, Ulisses Thorwald Moraes; Vilhalba, Eduardo Cabezudo; Neves, Danielly Cristina do Carmo; Quincozes, Silvio E. (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg), 2026)
The rising cost of cloud platforms has motivated students, hobbyists, and small teams to host low-demand applications in homelabs. Although this approach reduces costs and supports practical learning, exposing services from residential networks introduces security and availability risks. This paper presents a case study on securely exposing a homelab-hosted REST API using secure backend practices, a Dokku-managed Linux virtual machine, PostgreSQL, SSH hardening, and Cloudflare Tunnel. The results indicate that this architecture is a low-cost and replicable alternative for small applications, reducing direct network exposure while preserving encrypted access, centralized traffic handling, and a smaller attack surface.